Heinrich Schütz's Musikalische Exequien: Evidence of Influence - Johnston, Gregory (Canadian University Music Review / Revue de musique des universités canadiennes)

(untitled) (Canadian University Music Society / Société de musique des universités canadiennes, 1993)
Heinrich Schütz's Musikalische Exequien (SWV 279-81), written for the funeral of Prince Heinrich Posthumus von Reuß in 1636, is generally regarded as one of his finest works. Oddly, though, the praise accorded the composition has come almost entirely from critics of the last fifty years, while it is thought to have had negligible resonance in the seventeenth century. The present article suggests that the Exequien may in fact have been used as a model for three compositions by Michael Wiedemann in 1693. Based on comparisons of the circumstances which occasioned the works, on the identification of numerous shared compositional processes exclusive to these works in the seventeenth-century funerary repertory, on certain professional motivations, and on the logistics of publishing and geography which would have made the Exequien available to Wiedemann, it becomes possible to suggest with reason that Schütz's Musikalische Exequien was not without influence in baroque Germany.